Avaliação de polimorfismos em genes de citocinas no envelhecimento saudável, comprometimento cognitivo não demência e demência: uma abordagem cognitiva e funcional - Vanessa Gomes Fraga (2015)
Aging is a natural process potentially associated with the development of neurodegenerative disorders, causing cognitive impairment and dementia. It is possible that imbalances between the immune and nervous system influence the evolution of these processes. The Pietà study is an epidemiological investigation on brain aging, developed in Caeté (state of Minas Gerais), Brazil, involving oldest-old individuals (75 years). In order to identify the influence of cytokine gene polymorphisms and the occurrence of cognitive impairment no dementia (CCND) and dementia, and on cognitive and functional decline in elderly, 259 participants from the Pietà study were divided into three groups: cognitively healthy controls (n = 124), CCND (n = 81) and dementia (n = 54). Eight polymorphisms in five cytokines genes were studied: TNF-á -308G> A, TGF-â1 codon 10 C> T, TGF-â1 codon 25 G> C, IL10 -1082 A> G, IL-10 -819 C> T, IL-10 -592 C> A, IL-6 -174 G> C and INF-ã + 874T>A, using multiplex PCR. Genotypes were compared according to their distribution between the groups and considering the cognitive and functional performance of cross-sectional and longitudinal evaluations (after one year). Polymorphisms in TGF-â1 (10 C> T +25 G> C), IFN-ã (+ 874T> A) and IL-10 haplotype presented different distributions between the groups beyond influence together TNF-á (-308G> A) the cognitive and functional performance. On longitudinal analysis, the polymorphism +10C> T in the TGF-â1 gene could predict the cognitive and functional decline in the short-term among controls, and the polymorphism 174G>C in the IL-6 gene was associated with reduction of cognitive performance among CCND subjects within one year. These results suggest that genetic risk factors linked to inflammation may be associated with the development of CCND/dementia and deterioration of cognitive and functional abilities in oldest-old individuals. Thus, this study provides data for further research in order to elucidate the importance of the inflammatory process in dementia.